Scenes of Debris in Charles Fenestrier's La vie des frelons: The Conflict and Convergence of the Newspaper and the Novel at the fin de siècle. (November 2013) - Rees, Kate
Abstract : This article focuses on the conflicting images of the press in the fin de siècle years by way of the frequently employed metaphors of order and chaos, and dirt and cleanliness. It offers close analysis of a 1908 novel by the journalist Charles Fenestrier, La vie des frelons, which gives a detailed and satirical insight into the life of reporters in the offices of a large daily newspaper at the turn of the century. The newspaper is initially viewed as an impressive, streamlined vehicle with the capacity to organize and unify; but, as the novel progresses, it becomes clear that the new characteristics of a journalism increasingly linked to practices of reportage are in fact much more murky. At the same time, the boundaries between newspaper and novel become blurred. The more the novel rejects the new journalism, the more it is seen to borrow from its practices, both structurally and stylistically. In this text, patterns of order and debris give voice to a tense relationship between journalism and the novel, asking questions about the generic boundaries of each, as fiction and reportage conflict and coalesce.